Single‐Particle Spectroscopy of Alcohol‐to‐Olefins over SAPO‐34 at Different Reaction Stages: Crystal Accessibility and Hydrocarbons Reactivity. Issue 3 (March 2014) - Qian, Qingyun; Ruiz‐Martínez, Javier; Mokhtar, Mohamed; Asiri, Abdullah M.; Al‐Thabaiti, Shaeel A.; Basahel, Suliman N.; Weckhuysen, Bert M.
Abstract The front cover artwork for Issue 3/2014 is provided by the Inorganic Chemistry and Catalysis group of Utrecht University. The image shows the concept of synchrotron‐based IR and UV/Vis microspectroscopy monitoring a catalytic reaction on a single SAPO‐34 crystal and the obtained spatially resolved information on the retained hydrocarbon species and crystal accessibility. See the Full Paper itself on http://dx.doi.org/10.1002/cctc.201300962.